The legal regulation for issuing financing sukuk: Analytical study in the Saudi system - Al-Shikhi, Hoor Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to clarify the legal aspects of issuing financing sukuk in the Saudi financial market. Because of its important stages, the procedures of which have not been studied in detail and criticized; In the absence of clear legal regulation for it. To address the problem posed therein, this study followed the analytical approach, by analyzing the legal texts related to financing instruments in the Saudi financial market system and its implementing regulations. To demonstrate the appropriateness of these general procedures, usually related to all securities, to be applied to financing sukuk. This study reached conclusions, the most important of which is that the Saudi regulator did not stipulate any condition that must be met in the financing sukuk project or that the project be within the Kingdom of Saudi Arabia, whether the issuing authority is a Saudi or foreign company. Contracts subject to the provisions of Islamic law. In light of the results of this study, it recommended that the regulatory authorities organize the financing sukuk project and organize the documents and evidence necessary for it related to assets and assets located outside the Kingdom. It also stipulated the necessity of stipulating that the contracts issued in the financing instruments are contracts that are subject to the provisions of Islamic law, especially since the Kingdom adopts the provisions of Islamic law in its dealings.
Keywords: financing sukuk; Islamic sukuk; securities; issuance provisions; joint stock companies